2015
DOI: 10.1002/dta.1803
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of urine analysis and dried blood spot analysis for the detection of ephedrine and methylephedrine in doping control

Abstract: When the misuse of stimulants is determined in doping control tests conducted during the in-competition period, athletes are asked to account for the violation of the rules. This study was designed to evaluate whether the urinary threshold values (10 µg/mL) for ephedrine and methylephedrine set by the World Anti-Doping Agency (WADA) can be exceeded after the oral administration of each substance (25 mg). In addition, the study describes the validity of a liquid chromatography-tandem mass spectrometric method u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
37
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 24 publications
(37 citation statements)
references
References 40 publications
(94 reference statements)
0
37
0
Order By: Relevance
“…Among these materials, hair, sweat, saliva, urine and, currently, DBSs are some of these alternatives matrices that can be used in drug testing. [19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34] To verify that variations in FN1 concentrations could be detected in one DBS and urine after an rhGH administration, a pilot study with volunteers treated with a low dose of rhGH was performed. [38] Urine and DBSs were selected as potential matrices to be tested for the potential FN1 detection because they have provided promising results in the detection of a wide range of doping substances.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among these materials, hair, sweat, saliva, urine and, currently, DBSs are some of these alternatives matrices that can be used in drug testing. [19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34] To verify that variations in FN1 concentrations could be detected in one DBS and urine after an rhGH administration, a pilot study with volunteers treated with a low dose of rhGH was performed. [38] Urine and DBSs were selected as potential matrices to be tested for the potential FN1 detection because they have provided promising results in the detection of a wide range of doping substances.…”
Section: Discussionmentioning
confidence: 99%
“…[2,3] Alterations in FN1 levels have been associated with carcinomas, adenomas, myocardial infarction, Duchenne muscular dystrophy, and other diseases. [34] On the other hand, urine samples are ideal for biomarkers study because, despite containing low protein concentrations, the sample can be obtained non-invasively in a large volume and also sample collection can be performed by non-specialized personnel. [8,9] Previous results obtained in this area showed high mRNA expression levels of the FN1 gene after treatment with IGF-1 or rhGH in PBL samples and high FN1 protein levels after low rhGH doses in serum and plasma samples for a sustained time period (at least 7 days after end of rhGH treatment).…”
Section: Introductionmentioning
confidence: 99%
“…Following the oral administration of 365 μg of NN-DMPPA, urinary concentrations of up to 300 ng/mL were monitored within 2-3 h post application, and concentrations above 50 ng/mL were still observed after 24 h, outlining the difficulty of assigning the time of drug use to in-vs. out-of-competition periods. The fact that blood sampling, for example in the form of DBS, could facilitate decision-making processes particularly with regards to findings of compounds prohibited in-competition only was recently supported by a study by Kojima et al [143] The analysis of urinary concentrations of ephedrine and methylephedrine in controlled administration studies demonstrated that athletes might test negative (i.e. remain below applicable threshold values) for these substances up to 10 h post application but exceed respective threshold levels 12 h after ingestion of the stimulants, affected (amongst others) by urine flow and urinary pH.…”
Section: Stimulantsmentioning
confidence: 96%
“…out‐of‐competition periods. The fact that blood sampling, for example in the form of DBS, could facilitate decision‐making processes particularly with regards to findings of compounds prohibited in‐competition only was recently supported by a study by Kojima et al . The analysis of urinary concentrations of ephedrine and methylephedrine in controlled administration studies demonstrated that athletes might test negative ( i .…”
Section: Stimulantsmentioning
confidence: 99%
“…4 Ephedra alkaloids are commonly found in over-the-counter (OTC) products in addition to dietary supplements promoting weight loss and athletic performance. [5][6][7] It is known that some nutritional supplements can be contaminated with prohibited substances, which are not declared on the labels. 8 An international study revealed that 14.8% of 634 freely available supplements contained unlisted anabolic agents.…”
Section: Introductionmentioning
confidence: 99%